The communication patterns between the lateral antebrachial cutaneous nerve and the superficial branch of the radial nerve - Khadanovich, Anhelina; Herma, Tomas; Al-Redouan, Azzat; Kaiser, Radek; Kachlik, David (Annals of anatomy, 2023)
INTRODUCTION: The superficial branch of the radial nerve (SBRN) and the lateral antebrachial cutaneous nerve (LACN) are sensory nerves coursing within the forearm in a close relationship. This high degree of overlap and eventual communication between the nerves is of great surgical importance. The aim of our study is to identify the communication pattern and overlap of the nerves, to localize the position of this communication in relation to a bony landmark, and to specify the most common communication patterns. MATERIALS AND METHODS: One hundred and two adult formalin-fixed cadaveric forearms from 51 cadavers of Central European origin were meticulously dissected. The SBRN, as well as the LACN, were identified. The morphometric parameters concerning these nerves, as well as their branches and connections, were measured with a digital caliper. RESULTS: We have described the primary (PCB) and secondary communications (SCB) between the SBRN and the LACN and their overlap patterns. One hundred and nine PCBs were found in 75 (73.53%) forearms of 44 (86.27%) cadavers and fourteen SCBs in eleven hands (10.78%) of eight cadavers (15.69%). Anatomical and surgical classifications were created. Anatomically, the PCBs were classified in three different ways concerning: (1) the role of the branch of the SBRN within the connection; (2) the position of the communicating branch to the SBRN; and (3) the position of the LACN branch involved in the communication to the cephalic vein (CV). The mean length and width of the PCBs were 17.12 mm (ranged from 2.33 to 82.96 mm) and 0.73 mm (ranged from 0.14 to 2.01 mm), respectively. The PCB was located proximally to the styloid process of the radius at an average distance of 29.91 mm (ranged from 4.15 to 97.61 mm). Surgical classification is based on the localization of the PCBs to a triangular zone of the SBRN branching. The most frequent branch of the SBRN involved in the communication was the third (66.97%). Due to the frequency and position of the PCB with the third branch of the SBRN, the danger zone was predicted. According to the overlap between the SBRN and the LACN, we have divided 102 forearms into four types: (1) no overlap; (2) present overlap; (3) pseudo-overlap; and (4) both present and pseudo-overlap. Type 4 was the most common. CONCLUSION: The patterns of communicating branch arrangements appeared to be not just a rare phenomenon or variation, but rather a common situation highlighting clinical importance. Due to the close relationship and connection of these nerves, there is a high probability of simultaneous lesion.
Keywords: předloktí; Radial Nerve; nervus radialis; Cadaver; mrtvola; lidé; Radius; Adult; radius; dospělí; Hand; Forearm; Humans; ruka